تنشئة الطفل على فضيلة شكر الآخرين على معروفهم من منظور تربوي إسلامي - الجهنى، حنان بنت عطية الطورى (جامعة بغداد - مركز البحوث التربوية والنفسية, 2015)
هدفت الدراسة الى معرفة كيفية تنشئة الطفل على فضيلة شكر الاخرين على معروفهم من منظور تربوي إسلامي، ولتحقيق هذا الهدف استخدمت الباحثة المنهجين الاستنباطي، والوصفي بأسلوب الدراسات الوثائقية، وقد أظهرت النتائج أن الأطفال هم ثروة المجتمع الحقيقية، والقوة التي يعتمد عليها البناء الحضاري، والاهتمام بتنشئتهم مسؤولية لابد أن نشارك فيها الجميع، إن الشكر جزء من العقيدة الإسلامية، وهو من أعظم الفضائل الإسلامية، وفضيلة شكر الآخرين على معروفهم من أخلاق المؤمنين التي توثق الروابط، وتوسع شبكة العلاقات الاجتماعية الإيجابية، وتعد في أي مجتمع دلالة حضارية، ولها فوائد جمة تعود على الشاكر والمشكور، وأن هناك ضعف واضح في التوعية بأهمية فضيلة الشكر، وعوائدها الثمينة على مختلف الأصعدة، وأنه من أساليب تنشئة الطفل على فضيلة شكر الآخرين: أسلوب القدوة، والتوجيه والموعظة الحسنة، والترغيب والترهيب، وضرب الأمثال، والقصة، والممارسة والتعويد، والحوار، وإن غياب فضيلة شكر الآخرين على معروفهم إنما جاء نتيجة لعدد من العوامل التي من أهمها غياب القدوة الحسنة، وغياب الهدف من التربية، والإعلاء من شأن أمور سلبية على حساب القيم الأصيلة، وفي ضوء نتائج الدراسة خرجت الباحثة بعدد من التوصيات؛ كان من أبرزها: ضرورة إعادة بناء المنظومة الأخلاقية للأطفال بغرس فضيلة شكر الآخرين على المعروف في نفوسهم، وتعزيزها عن طريق مختلف أساليب التربية الإسلامية الأصيلة في البيت والمدرسة والمجتمع حتى تصبح أسلوب حياة، مع ضرورة مراعاة المشتغلين في ميدان المناهج والتطوير والتخطيط التربوي تضمين موضوع الشكر بصورة أكثر فاعلية في المناهج الدراسية في شتى مراحل التعليم العام والعالي، مع تشجيع البحوث العلمية المتخصصة والمتعلقة التي تتصل بفضيلة الشكر، والتي تتعلق بأدوار مختلف المؤسسات التربوية والمجتمعية في تنمية وتعزيز هذه الفضيلة مما قد يسهم في سد بعض الفراغ في مجال أصول التربية الإسلامية.
The study aimed to identify how to raise grateful children from an Islamic educational perspective. For that objective to be achieved, the researcher used both of deductive and descriptive approaches using the method of documentary research. The study's results show that children are the real wealth of the community and the foundation of cultural building; therefore, paying attention their raising is a responsibility that must be shared by everyone; gratitude is part parcel of the Islamic doctrine, which is one of the greatest virtues; the virtue of gratitude is the attitude of the believers which in turn strengthens the bonds and expands the network of positive social relationships; It is also considered a cultural significance in any community and has many rewards for both the grateful person and commendable person; there is obvious weakness among educators in terms of raising awareness among young people of the importance of gratitude virtue and its considerable rewards; and the Islamic methods for installing gratitude quality include: setting a role model, guidance, good advice, carrot and stick method, citing examples, storytelling, practice, habituation, and dialogue; and that the absence of gratitude was a result of a number of factors including the absence of setting a role model and the objective of education, while upholding the negative traits without regard for authentic values. In the light of the results of the study, the researcher came out with a number of recommendations including: the necessity to rebuild the moral system for children by instilling gratitude virtue in them, and strengthening it through various authentic Islamic educational methods at home, school and community so as to be a lifestyle, along with the necessity that who are engaged in the field of curriculum development and educational and planning development shall include the subject of gratitude more effectively in the academic curriculum in various stages of public and higher education and encouraging scientific and in-depth research related to the virtue of gratitude regarding the roles of the various educational and community institutions in the development and promotion of such virtue, which may contribute to fill the gap in the field of foundation of Islamic education.
772037
Keywords: التربية الإسلامية -- التنشئة الإسلامية -- رعاية الأطفال